ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DALAM MENETAPKAN HARGA JUAL PADA HOLLAND BAKERY BOULEVARD MANADO - Lumowa, Cindy Shelly; Tinangon, Jantje J.; Wangkar, Anneke (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Calculation of the cost of production is something that needs to be considered in determining the selling price of the product. Calculation of the cost of production that is right and accurate is something that needs to be done by every company, without a precise and accurate calculation of the cost of production, the manufacturing company concerned will experience in setting the selling price of a product. The purpose of this study was to determine the cost classification applied by Holland Bakery Boulevard Manado in calculating the cost of production, to find out the calculation of the cost of production of Holland Bakery Boulevard Manado in setting selling price and find out the determination of product selling price applied by Holland Bakery Boulevard Manado. Data analysis method used for this research is descriptive analysis method. The collection of cost of goods manufactured is the process cost method, while the method of determining the cost of production uses the full costing approach. There is a difference in the selling price per packet of bread between Holland Bakery Boulevard Manado with a theory caused by differences in the allocation of costs and determination of mark up between companies and theories. The company's selling price is lower than the theory that the difference for chocolate bread is Rp. 1.589, then for cheese bread Rp. 1.910, and for srikaya bread Rp. 2.449.